2010
DOI: 10.1016/j.bbr.2010.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neurotensin-2 receptor deletion on sensorimotor gating and locomotor activity

Abstract: SUMMARYEndogenous neurotensin (NT) has been implicated in brain processes relevant to schizophrenia as well as the therapeutic effects of antipsychotic drugs (APDs) used to treat this disorder. Converging evidence suggests that NT1 receptors mediate the antipsychotic-like effects of NT, such as prepulse inhibition (PPI) elevation. However, the role of NT2 receptors in these effects is not known. To investigate the contribution of NT2 receptors to the regulation of PPI, we measured baseline PPI and acoustic sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Based on these data, it appears that NTS1 and NTS2 do not play a role in the modulation of baseline PPI. A recent report by Feifel and collaborators examined baseline PPI in NTS2 -/-mice (Feifel et al, 2010a). The authors found that NTS2 -/-mice show higher baseline PPI as well as a lower ASR in comparison to WT mice and conclude that endogenous NT plays a role in regulating PPI via activation of NTS2.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on these data, it appears that NTS1 and NTS2 do not play a role in the modulation of baseline PPI. A recent report by Feifel and collaborators examined baseline PPI in NTS2 -/-mice (Feifel et al, 2010a). The authors found that NTS2 -/-mice show higher baseline PPI as well as a lower ASR in comparison to WT mice and conclude that endogenous NT plays a role in regulating PPI via activation of NTS2.…”
Section: Discussionmentioning
confidence: 99%
“…Some changes in knockout mice can be compensatory in nature. Recent reports by Feifel and collaborators do not implicate NTS1 in the disruption of PPI by d-amphetamine and dizocilpine, and attribute the regulation of baseline PPI to NTS2 (Feifel et al, 2010a;Feifel et al, 2010b). There are limitations that occur as a result of differences in environmental conditions between animal facilities and different experimental parameters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations